Applying sustainable urban drainage systems to urban floods management in area 49 planned settlement in Lilongwe City, Malawi - Mkombezi, Edda (School of Architecture, Planning and Geomatics, 2024)
This dissertation presents a research conducted by Edda Mkombezi titled: “Applying Sustainable Urban Drainage Systems to Urban Floods Management in Area 49 Planned Settlement in Lilongwe City, Malawi”. Currently, there is a frequent occurrence of urban floods in Lilongwe City with Area 49 being the most hit neighbourhood which is also the study area for this research. Therefore, this requires management using nature-based solutions such as Sustainable Urban Drainage Systems (SUDS). The main challenge is that SUDS and urban floods management are not adequately addressed in the current key spatial planning frameworks of Lilongwe City. There is a misalignment of the existing key spatial planning frameworks as far as SUDS implementation and integration are concerned. Thus, there is a need to examine what can be done in order to integrate SUDS into the key spatial planning frameworks. This includes addressing sustainable transition language, promoting participation of residents and re-imagining the role of spatial planning in water governance. The aim of this dissertation is to examine how SUDS can be integrated into the key spatial planning frameworks as a management mechanism for urban floods. This aim was achieved by collecting data through case study and discourse analysis methods. The collected data was then analysed using discourse analysis and content analysis. The results of this study show that there is room for the integration of SUDS in the key spatial planning frameworks but not as an urban flood management measure. Rather SUDS are being proposed as one of the climate-resilient infrastructure that the city needs. On the other hand, residents of Area 49 have their own knowledge and ways of managing urban floods which can be incorporated into the spatial planning frameworks. The language of sustainable transitions used in the key spatial planning frameworks is not comprehensive and misaligned. The knowledge gained from this study can inform policy review and formulation in disaster risk management and how spatial planning can be used in water governance of neighbourhoods in order to have proactive, context and site-specific responses to urban floods.